Beyond equal rights: Equality of opportunity in political participation - Paul Hufe; Andreas Peichl (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
It is well understood that political participation is stratified by socio-economic characteristics. Yet it is an open question how this finding bears on the normative evaluation of the democratic process. In this paper we argue that the equality of opportunity (EOp) concept furnishes an attractive framework to answer this question. Drawing on the analytical tools developed by an expanding empirical literature on EOp we investigate to what extent political participation is determined by factors that lie beyond individual control (circumstances) and thus is unfairly distributed. Using rich panel data from the US, we find that a lack of political opportunity is particularly pronounced for contacts with officials, participation in rallies and marches, and membership in political organizations. These opportunity shortages tend to complement each other across activities and persist over time. While family characteristics and psychological dispositions during childhood emanate as the strongest determinants, genetic variation is a small yet significant contributor to unequal political opportunities in the US.
urn:nbn:de:bsz:180-madoc-415256
Keywords: D39; D63; D72; 330; Equality of Opportunity; Political Participation; Genes